2006
DOI: 10.1021/ma052275a
|View full text |Cite
|
Sign up to set email alerts
|

Counterion Effect on the Rheology and Morphology of Tailored Poly(dimethylsiloxane) Ionomers

Abstract: We have carried out a systematic study of the time-dependent rheology and morphology of poly(dimethylsiloxane) (PDMS) ionomers with tailored number of monomers between ions and number of ions per chain as a function of the cation. Small-angle X-ray scattering (SAXS) and scanning transmission electron microscopy (STEM) were used to examine the structure of the samples. The flow behavior of nonequilibrated freshly precipitated ionomers varies from flowing liquids to weak networks. Low mol % zinc and cobalt ionom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…One other morphology has been noted in electron micrographs: rods with very small diameters and large aspect ratios [58]. These structures are seen only with poly (dimethyl siloxane) (PDMS) ionomers; along with the unique chemistry of PDMS compared to all of the hydrocarbon-based materials described earlier, the method of synthesis ensures that individual carboxyl groups are widely spaced.…”
Section: Compression Moldingmentioning
confidence: 96%
See 3 more Smart Citations
“…One other morphology has been noted in electron micrographs: rods with very small diameters and large aspect ratios [58]. These structures are seen only with poly (dimethyl siloxane) (PDMS) ionomers; along with the unique chemistry of PDMS compared to all of the hydrocarbon-based materials described earlier, the method of synthesis ensures that individual carboxyl groups are widely spaced.…”
Section: Compression Moldingmentioning
confidence: 96%
“…Mn atoms inside and outside of aggregates almost certainly do not have identical oxygen environments (especially with sixfold coordination, which was the case in this instance), and hence a much more reasonable interpretation is that the aggregation was so disordered that no SAXS peak appeared. More recent scanning transmission electron microscopy (STEM) studies [57,58] showed that materials that had no SAXS peak still had ionic aggregates. Spatial disorder and size polydispersity of these aggregates were clearly evident in STEM images and were likely responsible for no SAXS peak; contamination of ionic aggregates by organic material could have contributed as well.…”
Section: Ionomer Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of a shoulder on the upturn at low‐ Q between 0.01 and 0.10 Å −1 was observed earlier in various ionomers and was interpreted to be the classical “ionomer peak” arising from the ionic interaggregate interference . Ionic clusters of components with typical ≈20 nm sizes are known to exhibit two relaxation transitions in loss tangent profiles .…”
mentioning
confidence: 59%